Bioaccumulation of some essential metal concentration in Malaysian horseshoe crabs (tachypleus gigas) - Yunus, Kamaruzzaman; Megat, Aqilah; Akbar John, B. (IIUM Press, 2011)
We examined the selected essential metals (Fe and Zn) accumulative concentrations in different body parts of Malaysian horseshoe crabs [Tachypleus gigas (Muller, 1785)]. Metal accumulation levels were determined using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Average concentration (μg g-1 wet weight) of iron (Fe) and Zinc (Zn) were observed in gill tissue (1336.73±2.08 ppm) and apodeme (921.11±8.12 ppm) respectively. The lowest concentrations of metals were observed in gut (Fe = 556.61 ppm) and mouth (Zn = 605.36 ppm) tissue portions. Results clearly showed that bioaccumulation of both the essential metals were higher in the body parts but lower than the maximum permissible limit set by the national and international consortia. Statistical predictions revealed that bioaccumulation of metals were not significantly influenced by weight, total length and carapace width of the animal.